Transient measurement of the effective particle density of cigarette smoke. (September 2015) - Johnson, Tyler J.; Olfert, Jason S.; Cabot, Ross; Treacy, Conor; Yurteri, Caner U.; Dickens, Colin; McAughey, John; Symonds, Jonathan P.R.
Abstract: The real-time effective particle density of cigarette smoke was determined using a Centrifugal Particle Mass Analyzer (CPMA) and Differential Mobility Spectrometer (DMS). A Puff Inhale Exhale (PIE) simulator was used to produce the smoke from various research and commercial cigarettes following the International Standard Organization (ISO) puffing parameters (35 ml puff of 2 s duration, every 60 s) or the Health Canada Intense (HCI) puffing parameters (55 ml puff of 2 s duration, every 30 s). The impact of modifying parameters, such as smoke mass, cigarette format, filter type, inhalation volume and mouth hold period, on the effective particle density was also investigated. All of the effective density functions were found to be independent of particle size within the bias uncertainty of the measurement system, indicating that the cigarette smoke particles likely had a spherical morphology. Trends in the average effective particle densities were observed for the different cigarettes and puffing parameters. While all of these shifts were within the bias uncertainty of the CPMA–DMS system, two-sample t -tests and the Tukey method were used to identify where the shifts were statistically probable. However due to the complexity of cigarette smoke, the aerosol mechanisms behind most of these shifts were unknown and require further investigation. For all of the tested cases the average effective particle density, considering puffs 3–6, varied from 1090 to 1518 kg/m 3, with a majority (9 out of 16 cases) falling within 1300 to 1394 kg/m 3 . The Tukey method identified no statistical change in the effective particle density over the duration of an ISO puff, but it did identify significant differences between effective densities produced by different cigarettes. Highlights: The transient size-resolved effective density of cigarette smoke was measured. 16 different cases were studied, consisting of 5 puffing routines and 11 cigarettes. Over a base case puff, the effective density was constant within its uncertainty. Considering puffs 3–6, the effective density varied from 1090 to 1518 kg/m 3 . Considering puffs 3 to 6, 9 out of the 16 test cases fell within 1300–1394 kg/m 3 .